Drawing as a Creative Approach to Researching Extant Garments: A Case Study Involving John Ruskin's Clothing. (September 2020) - Mida, Ingrid; Casey, Sarah
Abstract : Reading the clues embedded in extant clothing demands both imagination and patience since the subtle marks of wear, use and alteration may only become evident with extended observation and reflection. During the course of a project undertaken in conjunction with the bicentenary celebrations of John Ruskin's birth culminating in the exhibition of Sarah Casey's drawings in Ruskin's Good Looking! (8 February–7 April 2019), the authors studied the garments of John Ruskin at Brantwood, his former home in the Lake District. The life-sized drawings of these garments produced by Casey mapped the absent presence of the former wearer, allowed visitors the opportunity to better see and reflect on Ruskin's clothing, and also revealed the hidden histories of Ruskin's garments. Drawing, the making of marks with meaning, is not an obvious research tool in dress history and curatorial practice but, as this case study shows, can expose subtle details and reveal new insights.